Age at first sexual intercourse and frailty: Mendelian randomization and population-based evidence from NHANES and UK Biobank - Kai-Xian Wang; Bao-Peng Liu; Jia-Ning Wang; Kai-Zheng Wang; Yi-Zhan He; Meng-Yao Yu; Zi-Ming Shao; Long Sun; Mei-Xia Xu (Sexual Medicine, 2026)
Abstract Introduction Age at first sexual intercourse (AFS) is an indicator of sexual initiation and may reflect broader life-course trajectories, but its relationship with frailty remains unclear. To examine genetic evidence for a potential association between AFS and frailty and to characterize nonlinear, threshold, and sex-specific patterns in population-based observational analyses. Methods We performed Mendelian randomization (MR) analyses using summary statistics for AFS and frailty. We further analyzed data from the National Health and Nutrition Examination Survey (NHANES; n = 8282) and UK Biobank (UKB; n = 109 449) among participants aged 50 years or older with AFS ≥15 years. Participants reporting AFS <15 years were analyzed separately. Frailty status was defined using a frailty index cutoff of >0.21, and the nonlinear and threshold associations between AFS and frailty. Results MR analyses showed that genetically predicted earlier AFS was associated with higher frailty risk (β = -0.30; 95% CI, -0.36 to -0.25), with similar estimates in males (β = -0.23; 95% CI, -0.30 to -0.16) and females (β = -0.22; 95% CI, -0.30 to -0.13). In observational analyses, restricted cubic spline models showed significant L-shaped associations between AFS and frailty in both NHANES and UKB. AFS <15 years was not significantly associated with frailty in the overall analyses. Compared with the third quintile of AFS, participants in the first and second quintiles had 61% (OR = 1.61, 95% CI: 1.40-1.85) and 19% (OR = 1.19, 95% CI, 1.05-1.41) higher odds of frailty, respectively, whereas fifth quintiles had 23% (OR = 0.77, 95% CI, 0.64-0.91) lower odds of frailty in NHANES; participants in the first quintile had 34% (OR = 1.34, 95% CI, 1.18-1.52) higher odds of frailty in UKB. Threshold analyses identified integer cut points of 21 years in NHANES and 23 years in UKB. Below these thresholds, later AFS was associated with lower odds of frailty; above them, associations were not statistically significant. Conclusion MR analyses provided genetic evidence consistent with a potential association between earlier AFS and higher frailty risk, while population-based analyses showed an L-shaped association among middle-aged and older adults. These findings should be interpreted cautiously and not as definitive evidence of causality. Earlier AFS may be relevant to frailty risk later in life, supporting safe, informed, and rights-based sexual development rather than defining an optimal age for sexual debut.